O humanismo torguiano em Novos Contos da Montanha - Loureiro, Adriano [UNESP] (2014)
Miguel Torga (1907-1995), one of the most important Portuguese writers of the twentieth century, is situated between Presencismo and Portuguese Neorealism, surpassing the limitations of both literary movements and, through his language, encompasses individual subjectivism and social concerns, providing him with a universal character. We will analyze Novos Contos da Montanha (1944), with the intention of pondering on Torga’s literature and comprehending the expression Man in his short narratives, as well as in his verse and autobiographic texts, with the support of critics such as Eduardo Lourenço, José de Melo and Carlos Carranca. Our analysis is guided by three elements (tellurism, religiosity and suffering). Even though these elements can be found in all of the twenty two stories of that collection, we justify this to better undertand the artist’s literary project, which we name torguian humanism